Exploration of social determinants of health and prostate cancer prevalence in the US: a cross-sectional study of NHANES data from 2003 to 2010 - Hu, Danfei; Chen, Xiaodong; Li, Mingyao; Xiong, Huacai; Lu, Xuefeng; Chen, Feng (Frontiers in Public Health, 2025)
ObjectiveSocial determinants of health (SDoH) are increasingly recognized as key factors in addressing health inequities. This study aimed to explore the association between SDoH and risk of prostate cancer (PCa).MethodsWe analyzed data from the National Health and Nutrition Examination Survey 2003–2010. PCa diagnosis was based on self-reported questionnaires, while highly-probable PCa was assessed using prostate-specific antigen levels. Multivariate logistic regression, restricted cubic spline, and subgroup analysis were performed. Three models were employed: the crude model (unadjusted), model 1 (adjusted for age and race/ethnicity), and model 2 (further adjusted for body mass index, alcohol consumption, and smoking status).ResultsThe median age of 5,633 participants was 54 years. A negative association was found between the SDoH score and PCa prevalence (OR = 0.868, 95% CI: 0.786–0.959, p = 0.006). Specifically, a family income-to-poverty ratio < 3 (OR = 0.69, 95% CI: 0.499–0.954, p = 0.029) and lack of healthcare access or reliance on emergency rooms (OR = 0.429, 95% CI: 0.218–0.842, p = 0.017) were independently associated with lower PCa prevalence. In model 2, no significant association was found between SDoH and highly probable PCa. A linear association between SDoH and PCa prevalence was observed. A consistently negative association was noted among participants aged ≥ 60 years, Non-Hispanic Black, Non-Hispanic White, and non-obese individuals.ConclusionsThe negative association between SDoH and PCa prevalence is likely attributable to inadequate screening and underreporting, rather than any protective effects. Unfavorable SDoH is not a risk factor for the onset of PCa. This study underscores the importance of addressing disparities in healthcare access and improving equity in PCa screening.